ANALISIS KEPUASAN KONSUMEN TERHADAP PELAYANAN KEFARMASIAN DI APOTEK PUSPA INDAH FARMA DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Ardianto, Nanang; Sekti, Beta Herilla (Journal Medicine And Clinical Pharmacy, 2024)
Pharmaceutical services are a benchmark for pharmaceutical technical personnel in services at pharmacies in order to improve quality of life, quality service and consumer satisfaction. The aim of this research to determine satisfaction with each item in pharmaceutical services at Puspa Indah Farma pharmacy. This research involved 100 consumers who purchased prescription drugs cash at Puspa Indah Farma Malang Pharmacy using Importance Performance Analysis (IPA) method. The research design used was descriptive quantitative "non-experimental". The results obtained in reliability dimension were all very satisfied category. The responsiveness dimension received scores that were all very satisfied category. The guarantee dimension received a score where all of them were in very satisfied category. From the empathy dimension, all of them were very satisfied category. From the direct evidence dimension, all scores were in the very satisfied category. Based on the science analysis of Cartesian diagram, there are no items included in quadrant I, quadrant II is occupied by items number 1,5,6,7,8,10,11,12,14,15 and 16, quadrant III item number 17,18, 19, and 20. Quadrant IV items number 2,3,4,9, and 12. From the results of the research conducted it can concluded that there are no items need to be improved, However, 11 items must maintained.